Conselho escolar e a configuração de uma democracia contra-hegemônica na gestão da escola pública: considerações a partir do princípio da comunidade - Cavalcante, Maria do Socorro Silva (2014)
This work has as its object of study the school board as a possibility for democratization of the management of the public school in the prospect of building a democracy to counter-hegemonic liberal model, which has community as its core/spindle. The work was theoretical and methodological supported by procedures mentioned by Boaventura de Sousa Santos (2002, 2006, 2007, 2010, 2011), Santos; Avritzer (2002) and Santos; Meneses (2009), such as the sociology of absences, the sociology of emergences and translation work. The research seeks to answer the following question: before the clashes, advances and retreats around the construction of democracy in Brazil, had the School Board constituted a possibility of democratization of the management of public schools, from the community? We start from the assumption that knowledge silenced in the global South are produced as nonexistent, requiring ecology of knowledge and procedure of the sociology of absences and the sociology of emergences to elicit it, generating a range of other learning with ability to think better and possible future. All knowledge, evidenced from the sociology of absences and sociology of emergencies, need to talk to another, becoming an intercultural dialogue possible made intelligible through the work of translation. Based on this theoretical and methodological framework, we analyze the experience of the School Board at a public school in the João Pessoa s municipal education network where signals realize the political potential of the individuals who make up the community through the School Board, constituting itself as a possibility of building a democracy to counter-hegemonic liberal model of management of public schools. This is a qualitative research, with the empirical field of a school Municipal João Pessoa-PB, whose experience of School Board signals evidence of democratic practices in the performance of board members. As instruments for data collection we used semi-structured interviews, observation and field diary, taking as reference the performance possibilities of the council as a political instrument magnification of emancipatory practices of democratic participation, signaling the possibility of democratic management public school. We start from the understanding of the community categories, democracy and democracy counter-hegemonic, with investments in Santos (2002, 2006, 2007, 2010, 2011), Santos; Avritzer (2002) and Santos; Meneses (2009). Democratic management according to Paro (2000), Cury (2002), Freitas (2007) and Andrade (2011). School boards in the perspective of Adrião; Campbell (2001), Werle (2003) and Marques (2011). From this perspective, the School Board, here understood as a political instrument of democratic management of public schools articulated to the school community, is a possibility not yet fully explored, in view of the regulatory community pillar, within the paradigm of Western modernity, pointed out by Santos (2002, 2006, 2007, 2010, 2011), Santos; Avritzer (2002) and Santos; Meneses (2009)